THE IMPACT OF BRAND TRUST AND BRAND AFFECT ON BRAND LOYALTY AT POND’S SKIN CARE MANADO - Lolowang, Anggreiny C.; Mekel, Peggy Adeline (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Brand is not just a brand for a product or service on the market. Brand makes consumers buy and use the brand. To introduce a product publicly the market, company should create a good reputation for brand. Research objectives are to analyze the influence of brand trust on brand loyalty and to analyze the influence of brand affect on brand loyalty. This research implement quantitative analyze by using questionnaires and used Multiple Regression analyze. The population observed is people in Manado specially woman who use Pond’s skin care with sample as many as 100 respondents. Result and conclusion show that brand trust and brand affect have significant effect on brand loyalty. Brand trust has positive and significant impact on Brand Loyalty on Pond's beauty products. Brand Affect has positive and significant impact on Brand Loyalty on Pond's beauty products. However, the analysis result has proof to show the impact of brand trust and brand affect on brand loyalty. Keywords: brand trust, brand affect, brand loyalty